Ultrafast dynamics in dimeric hemoglobin probed by time-resolved resonance Raman spectroscopy - Gao, Xiang (2020)
Time-resolved anti-Stokes Raman spectroscopy is selective for vibrationally excited modes, and it is therefore a powerful method for measuring vibrational energy relaxation.1-2 The intensity ratio of anti-Stokes and Stokes scattering is expected to provide the most direct information about relative vibrational populations. Here, we applied this technique to explore the vibrational energy relaxation of heme in the globin matrix upon ligand photodissociation of Scapharca inaequivalvis dimeric hemoglobin (HbI).